Exploration of Student Algebraic Thinking In Terms Of Implusive Reflective Cognitive Style - Lughina A'yun Zahrotu Najma; Masduki Masduki (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
Algebra is the part of mathematics that helps represent problems. Learning algebra is crucial since it has numerous applications outside of mathematics and in daily life. The subject of algebra is one that students need to master. The purpose of this study was to reveal the ability of algebra students' thinking profiles in solving math problems in terms of cognitive style reflective and impulsive. The subjects of this study were 32 students at a university in Surakarta. The method used in this study is a qualitative method with a case study approach. The instruments in this study were the MFFT test (Matching Familiar Figure Test), algebraic tests, and interviews. The results showed that 1) Students who have a reflective cognitive style and students who have an impulsive cognitive style can fulfill two indicators of algebraic thinking, namely functional thinking, generalization, and justification. 2) Students who have a reflective cognitive style are more systematic in working on problems. Meanwhile, students who have an impulsive cognitive style are more likely to write only the final result. Keywords: algebra thinking, cognitive, reflective-impulsive